Nilai Karakter Respect Siswa Kelas Rendah di SD Negeri 2 Bendungan Gondang Tulungagung - Firnadekalusi; Oktaviarini, Nourma (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
The character value of respect for students contains the character values of affection, humility, honesty, tolerance. The application of the character of respect students is good, it can be seen that students apply the character indicator of respect. The purpose of the study describes the Application of The Character Value of Respect for Low Grade Students at SD Negeri 2 Dam. Qualitative type of research phenomenogic approach. Collection of observational data, interviews, documentation. The results of the study on the character value of respect for low-grade students are: recapitulation of the average character value of students' respect, honorific aspects of 91%. The award aspect is 84%. The respect aspect is 70%. Aspect of friendliness 83%. Aspects of harmony 89%. The aspect of politeness is 78%. Aspects of manners attitudes 88%. Conclusion 1) honorific: the student uses polite language to the interlocutor; 2) awards: students appreciate every difference; 3) respect: students behave respectfully by appreciating actions; 4) friendliness: students show friendly behavior to others; 5) harmony: students keep the peace of their fellow friends so as not to quarrel; 6) politeness: students are polite to friends and others; 7) manners attitude: students behave well and obey school rules.